Motivation and Compensation Effects on Employees Performance in The Directorate General of Horticulture, Ministry of Agriculture Jakarta - Usman, Ansar; Sutopo, Sriyono Joko; Rahimullah, Rahimullah (International Journal of Social Service and Research, 2023)
This study aims to analyze the influence and provision of compensation on employee performance of the Directorate General of Horticulture, Ministry of Agriculture, Jakarta, namely by how employee performance is carried out with motivation and compensation. In addition, the research is limited to the object of research, namely the Directorate General of Horticulture, Ministry of Agriculture, Jakarta. This study uses a quantitative method with explanatory research type, with a population of 341 employees and a research sample of 77 people determined by the Slovin formula. The data collection technique in this study was a questionnaire and library technique. The research hypothesis proves that there is a significant and positive effect of motivation and compensation on employee performance at the Directorate General of Horticulture, Ministry of Agriculture, Jakarta. Based on the results of the study, it can be said that there is a significant and positive effect on employee performance of 77.4% and there is a significant and positive influence on employee performance of 76.4%, where together there is a significant influence and positive motivation. compensation for employee performance is 85.4%.